Further evaluation and validation of a commercially available competitive ELISA (cELISA) for the detection of antibodies specific to equine arteritis virus (EAV). (23rd January 2016) - Pfahl, K.; Chung, C.; Singleton, M. D.; Shuck, K. M.; Go, Y. Y.; Zhang, J.; Campos, J.; Adams, E.; Adams, D. S.; Timoney, P. J.; Balasuriya, U. B. R.
Abstract : The purpose of this study was to further evaluate and validate two commercially available equine arteritis virus (EAV) competitive ELISAs (original and enhanced cELISAs) using archived equine sera from experimentally inoculated animals and field sera submitted for laboratory diagnosis. First, the original and subsequently enhanced cELISAs were compared with the virus neutralisation test (VNT) using a panel of archived serum samples from experimentally inoculated animals. Then, the enhanced cELISA was compared with the VNT using a large panel of archived serum samples. The total number of equine sera tested was 3255, which included sera against 25 different EAV strains. The study confirmed that the enhanced cELISA was more sensitive than the original cELISA. Based on testing sera from experimentally inoculated animals and field sera, the enhanced cELISA had an estimated sensitivity (98.9 percent and 99.6 percent, respectively) and specificity (98.3 percent and 98.7 percent, respectively). The currently marketed enhanced VMRD EAV antibody cELISA test kit (VMRD Inc., Pullman, Washington, USA) has high sensitivity and specificity relative to the VNT. Based on the findings of this study, the authors would propose that the enhanced cELISA should be considered as an alternative approved method to the VNT for the detection of antibodies to EAV.